Negotiating preferential market access : the case of NAFTA - Estevadeordal, Antoni (IDB-INTAL Buenos AiresAR, 1999)
Examines the relationship between the two most important market access instruments in the area of NAFTA negotiations : the preferential tariff phase-outs and the accompanying rules of origin.